Kinematic Analysis of a Drinking Task in Chronic Hemiparetic Patients Using Features Analysis and Statistical Parametric Mapping - Santos, Gabriela Lopes; Russo, Thiago Luiz; Nieuwenhuys, Angela; Monari, Davide; Desloovere, Kaat (Archives of physical medicine and rehabilitation, 2018)
To compare sitting posture and movement strategies between chronic hemiparetic and healthy subjects while performing a drinking task, using statistical parametric mapping (SPM) and feature analysis. Cross-sectional study. A university physical therapy department. Participants (N=26) consisted of chronic hemiparetic (n=13) and healthy individuals (n=13) matched for sex and age. Not applicable. The drinking task was divided into phases: reaching, transporting the glass to mouth, transporting the glass to table, and returning to initial position. An SPM 2-sample t test was used to compare the entire kinematic waveforms of different joint angles (trunk, scapulothoracic, humerothoracic, elbow). Joint angles at the beginning and end of the motion, movement time, peak velocity timing, trajectory deviation, normalized integrated jerk, and range of motion were extracted from the motion data. Group differences for these parameters were analyzed using independent t tests. At the static posture and beginning of the reaching phase, patients showed a shoulder position more deviated from the midline and externally rotated with increased scapula protraction, medial rotation, anterior tilting, trunk anterior flexion and inclination to the paretic side. Altered spatiotemporal variables throughout the task were found in all phases, except for the returning phase. Patients returned to a similar posture as the task onset, except for the scapula, which was normalized after the reaching phase. Chronic hemiparetic subjects showed more deviations in the proximal joints during seated posture and reaching. However, the scapular movement drew nearer to the healthy individuals' patterns after the first phase, showing an interesting point to consider in rehabilitation programs.